Controlling Aedes spp Mosquito Larvae, the Vector of Dengue Hemorrhagic Fever (DHF), in Jatingarang Village, Sukoharjo - Bella Hasnia Cahyaningrum; Diah Ayu Kusuma Wulandari; Maulana Habib Wicaksono; Ririn Nur Hidayati; Wasiatul Karimah; Annisa Dewi Cahya; Bela Segar Juniarti; Mitoriana Porusia (Universitas Muhammadiyah Surakarta, 2025)
Dengue Hemorrhagic Fever (DHF) is one of the infectious diseases transmitted by the Aedes aegypti mosquito which is still endemic in Indonesia. DHF is still a priority disease that needs to be addressed by the Sukoharjo Health Office, especially in the Weru District. Based on the results of the Self-Reflection Survey (SMD) on residents of Dusun 1, Jatingarang Village, Kabupaten Sukoharjo with a total sample of 152 households, it was found that 63.2% or 92 households still had insufficient knowledge about DHF. This community service activity carried the theme Smart mother Education Program, which consisted of two main activities: increasing community knowledge about DHF and utilizing Abate to eradicate mosquito larvae as an effort to control DHF. The first activity involved providing education about DHF to 30 participants. The results of the analysis using the Wilcoxon test showed a p-value of 0.000 (≤ 0.05), which means there is a significant difference in the participants' knowledge scores before (pre-test) and after (post-test) the delivery of the material. The frequency distribution shows an increase in the good knowledge category, from 18 people (60%) before education to 23 people (76.7%) after education. The second activity was the door-to-door distribution of Abate to 33 houses where mosquito larvae were positively found. In addition, the Larva Free Index (ABJ) in Dusun 1 increased from 80.2% to 94.8%, indicating an improvement in the success of mosquito larva control. This program effectively increased community knowledge about DHF and the use of Abate for mosquito larva eradication, and it successfully improved the Larva Free Index in Dusun 1, Jatingarang Village.